Comparing the effectiveness of video self-instruction versus traditional classroom instruction for learning cardiopulmonary resuscitation skills among first year medical students in Universiti Sains Malaysia - Marcus, Mexmollen (Pusat Pengajian Sains Kesihatan, 2020)
ABSTRACT Introduction: Out of Hospitals Cardiac Arrests (OHCA) is a current concern however public awareness to perform bystander cardiopulmonary resuscitation (CPR) is poor. A majority of medical-based students face the same problem due to minimal exposure in their curriculum. Existing CPR teaching courses are costly, time consuming, instructor dependent and subject to availability. This study was to determine association between the acquisition of a competent overall CPR performance and two teaching modules, video self-instruction (VSI) module and the traditional classroom instruction (TCI) module. Methods: This randomized prospective interventional study involved freshmen of the health campus in Universiti Sains Malaysia (USM), from November 2018 until January 2019. Data collected included pass-fail scores representing the overall CPR and individual skill performance, and willingness to perform CPR before and after the training module for strangers and family members. Participants were randomized into two groups, VSI and TCI. Post training assessment of participants CPR competency was done. Factors associated with reluctancy to perform CPR for strangers and family members were assessed in a questionnaire. Results: A total of 99 participants were included. There were 50 VSI and 49 TCI participants. Comparable mean passing scores and rates for both VSI (3.69, 90%) and TCI (3.91, 96%) were recorded (p = 0.436). VSI participants performed comparably with their TCI counterparts in 8 out of 12 individual CPR skill sets. Both modules demonstrated significant improvement in willingness to perform CPR from before to after training for different scenarios (p < .001). Willingness to perform CPR for strangers (p = 0.999) and family members (p = 0.117) between both modules were comparable. Lack of training was noted to be the main hindrance factor to perform CPR for the majority of participants. Conclusions: The VSI CPR training module is an effective method to help students to be competent and willing to perform CPR and is comparable to the TCI CPR training module. It can be used as an independent or supplementary teaching tool for first time learners not only for students in higher learning institutions, but also for laypeople who have difficulties to access this knowledge. The VSI CPR training module’s greatest utility as when it is used as a standardized CPR refresher material that is easily accessible, as well as cost and time effective.